Assessing the air cargo business models of combination airlines. (October 2016) - Reis, Vasco; Silva, João
Abstract: Notwithstanding the fact that the air cargo business is generally a secondary one to the passenger business for combination airlines, it can have an important role to play in their profitability. However, growing challenges are threatening the market positions of the combination airlines. Improving their market positioning depends, amongst other factors, on appropriate business models. Yet, the literature on the air cargo business models of combination airlines is scarce. This paper aims to contribute to closing this gap. The research presented herein aimed to identify the representative business models of the combination airlines' cargo strategies. Three strategies have been considered. The research method included a series of structured interviews with key informants from combination airlines, namely: TAP Cargo, Brussels Airlines Cargo, SATA Cargo, Turkish Cargo, SWISS WorldCargo, Finnair Cargo, AF-KLM Cargo, Emirates SkyCargo, Lufthansa Cargo and IAG Cargo. The ten air cargo business models and the representative business models of each strategy are described. The results suggest an overlap between the business models of different strategies. In addition, the results show that an evolution in strategy does not necessarily require a redesign of the business model, but tailored changes in specific components. Highlights: Ten business models of combinations companies' cargo business are described. Business models of three representative cargo strategies are proposed. Overlap and similarities amongst representative business models were found. Alterations on specific elements of business model can lead to a strategy evolution.